Ludicidade e TIC: caracterização da webquest como uma metodologia lúdica no ensino de ciências - Pereira, Larissa Santos (2014)
The use of Information and Communication Technologies (ICT), particularly of internet, is common present in contemporary society as an important communication aspect. Thus, the ICT can be important in the school context if they are linked a playful elements to the educational context, because when these technological elements present characteristics like freedom, they raise the interest of students. In this perspective, the webquest emerges as a methodology that provides a roadmap of research, in which the teacher structures all the process of knowledge construction, whith a definition of a task. This aimed of this research was to characterize the webquest as a ludic activitie, investigating their potential contributions to science education. For this, was a qualitative research from a documentary survey in magazines qualis A1, A2 and B1 seeking webquest related to teaching science and / or biology articles was performed. 17 articles analyzed in the light of Textual Discourse Analysis, allowed the inference of some characteristics presented in the literature as indicators of ludicity, are also present in the webquest were selected. Thus, the webquest presents itself as an important recreational methodology for student learning in science education.